1994
DOI: 10.1017/s0022112094003721
|View full text |Cite
|
Sign up to set email alerts
|

On the instabilities of vertical falling liquid films in the presence of surface-active solute

Abstract: A linear-stability analysis is performed on a vertical falling film with a surface-active solute. It is assumed in the present model that the surfactant is soluble and volatile. In addition to the surface wave mode and the ‘wall wave’ mode which originate from the gravity-driven flow of the falling film itself, a new mode of instability related to the Marangoni effect induced by surface tension gradients is found for low Reynolds numbers and for moderate- or short-wavelength disturbances. The new mode is thoug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
36
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 10 publications
0
36
0
Order By: Relevance
“…This result was obtained for a vertically falling film by Anshus and Acrivos [9], who also showed that the wavelength of the most dangerous mode is significantly increased by surfactant. Ji and Setterwall [10] discussed the effect of soluble surfactant and demonstrated the existence of an unstable Marangoni mode for a vertical film. Pozrikidis [11] relaxed the long-wave assumption adopted by previous workers and showed that for a single film in the inertialess, zero Reynolds number limit, there are two normal modes, the first of which corresponds to that found by Yih [4] and the second of which is a Marangoni mode contributed by the surfactant.…”
Section: Introductionmentioning
confidence: 99%
“…This result was obtained for a vertically falling film by Anshus and Acrivos [9], who also showed that the wavelength of the most dangerous mode is significantly increased by surfactant. Ji and Setterwall [10] discussed the effect of soluble surfactant and demonstrated the existence of an unstable Marangoni mode for a vertical film. Pozrikidis [11] relaxed the long-wave assumption adopted by previous workers and showed that for a single film in the inertialess, zero Reynolds number limit, there are two normal modes, the first of which corresponds to that found by Yih [4] and the second of which is a Marangoni mode contributed by the surfactant.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, the flow in falling liquid films has been studied extensively through experimental measurements [10,45], low-dimensional modelling [46,47], and full numerical simulations [48]. The effects of many factors that influence the flow in falling films have been investigated, such as the effects of thermocapillarity [49], electric fields [50,51], and surfactants [52,53]. Different processes that may be involved in falling films have also been studied, such as heat transfer [54], mass transfer [55], chemical reactions [56], and phase change [57].…”
Section: Introductionmentioning
confidence: 99%
“…Mass transfer rates, as well as the kinetics of adsorption, have been shown to be critical in the special case of a volatile soluble surfactant, which actually enhances instability (Ji & Setterwall 1994;Shkadov, Velarde & Shkadova 2004). Enhancement of instability was also shown by Yiantsios & Higgins (2010) to be possible under conditions of evaporating thin films in the presence of non-volatile soluble surfactants.…”
mentioning
confidence: 99%